A Prophetic Trajectory: Ideologies of Place, Time and Belonging in an Angolan Religious Movement - Blanes, Ruy Llera ([s.n.], 2014)
Combining ethnographic and historical research conducted in Angola, Portugal, and the United Kingdom, A Prophetic Trajectory tells the story of Simão Toko, the founder and leader of one of the most important contemporary Angolan religious movements. The book explains the historical, ethnic, spiritual, and identity transformations observed within the movement, and debates the politics of remembrance and heritage left behind after Toko's passing in 1984. Ultimately, it questions the categories of prophetism and charisma, as well as the intersections between mobility, memory, and belonging in the Atlantic Lusophone sphere